Could Azithromycin Be Part of Pseudomonas aeruginosa Acute Pneumonia Treatment? - Leroy, Anne-Gaëlle; Caillon, Jocelyne; Caroff, Nathalie; Broquet, Alexis; Corvec, Stéphane; Asehnoune, Karim; Roquilly, Antoine; Crémet, Lise (Frontiers in Microbiology, 2021)
Azithromycin (AZM) is a 15-membered-ring macrolide that presents a broad-spectrum antimicrobial activity against Gram-positive bacteria and atypical microorganisms but suffers from a poor diffusion across the outer-membrane of Gram-negative bacilli, including Pseudomonas aeruginosa (PA). However, AZM has demonstrated clinical benefits in patients suffering from chronic PA respiratory infections, especially cystic fibrosis patients. Since the rise of multidrug-resistant PA has led to a growing need for new therapeutic options, this macrolide has been proposed as an adjunctive therapy. Clinical trials assessing AZM in PA acute pneumonia are scarce. However, a careful examination of the available literature provides good rationales for its use in that context. In fact, 14 and 15-membered-ring macrolides have demonstrated immunomodulatory and immunosuppressive effects that could be of major interest in the management of acute illness. Furthermore, growing evidence supports a down-regulation of PA virulence dependent on direct interaction with the ribosomes, and based on the modulation of several key regulators from the Quorum Sensing network. First highlighted in vitro, these interesting properties of AZM have subsequently been confirmed in animal models. In this review, we systematically analyzed the literature regarding AZM immunomodulatory and anti-PA effects. In vitro and in vivo studies, as well as clinical trials were reviewed, looking for rationales for AZM use in PA acute pneumonia.